Analisis Ordo Integrasi Beberapa Peubah Ekonomi - Budiman Hutabarat; nFN Sumedi (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2001)
EnglishCointegration analysis has drawn economists' attention in dealing time series data, but the validity of its results is subject to the integration property of variables being considered. The paper is an effort to investigate the order of integration of times series economic indicators that are important to agricultural sector. The research concludes that all variables analyzed fall into the group of integrated of order one, as their first-differenced transformations are all stationary. With this finding it is theoretically sound to formulate regression among related economic variables.IndonesianAnalisis kointegrasi telah semakin populer di kalangan analis ekonomi dalam menghadapi data deret waktu, tetapi kesahihan hasil-hasilnya dipengaruhi oleh sifat integrasi peubah yang di pertimbangkan. Makalah ini merupakan satu upaya untuk menyelidiki ordo integrasi indikator ekonomi yang ada kaitannya dengan sektor pertanian. Penelitian ini menyimpulkan bahwa semua peubah yang dianalisis termasuk dalam kelompok berordo integrasi satu, karena semua transformasi, beda pertamanya bersifat stasioner. Dengan penemuan ini, secara teoritis dapatlah dirumuskan regresi antara peubah ekonomi yang berkaitan.